Other risk factors associated with mortality in moderate and severe cystic fibrosis patients - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (TURKISH PEDIATRICS ASSOC, 2012)
Aim: Severe pulmonary disease is responsible for over 80% of deaths associated with cystic fibrosis. Our aim was to evaluate the other risk factors associated with mortality in patients with cystic fibrosis who have moderate and severe lung disease. Material and Method: Among 200 patients with cystic fibrosis who were followed up in our clinic, 35 patients with moderate and severe lung disease (%FEV1 predicted <= 60) were included in the study. Demographic data, pulmonary function tests, high resolution thorax tomography, modified Bhalla score, blood gas analysis and nutritional status of the patients were evaluated. Results: Requirement for respiratory support was 31.4% in moderate and severe lung disease. Lower pulmonary function, requirement for non invasive ventilation, presence of diabetes mellitus, a SaO(2) value of <95, a value of pCO(2) >50 mm Hg and requirement for frequent IV antibiotics were significantly related with increased mortality. Conclusions: This is a single centre study conducted in patients with cystic fibrosis who had moderate and severe lung disease and who had not received lung transplantation. We evaluated the clinical outcome and other factors that were associated with mortality. (Turk Arch Ped 2012; 47:267-71)
Keywords: Child; cystic fibrosis; risk of mortality; LUNG TRANSPLANTATION; PSEUDOMONAS-AERUGINOSA; TURKISH; MUTATIONS; CHILDREN; PREDICTORS; SURVIVAL